(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Aims: This study was designed to evaluate postoperative morbidity in patients underwent microdebrider intracapsular tonsillotomy as compared with Cold steel dissection tonsillectomy. Patients and Methods: This prospective randomized clinical trial study was carried out in Al-Hilla General Teaching Hospital during the period from March 2017 to July 2018. This study included 40 patients between the age of 4–38 years, requiring tonsillectomy for variable indications. Cold steel dissection tonsillectomy on the right tonsils was compared to microdebrider intracapsular tonsillotomy on left tonsil. We took informed consent from patients and parent after describing operation technique and possible complications. Results: On postoperative days one to 10, patients notes significantly a whole lot much less pain on the microdebrider intracapsular tonsillotomy side in comparison with the Cold steel dissection tonsillectomy side. By postoperative days 11th to 14th, the distinction among aspects disappeared. Twenty-eight patients (70%) mentioned otalgia, and and it became always unilateral. For those patients mentioned otalgia, there has been a 100% correlation among the aspect of otalgia and the aspect of Cold steel dissection tonsillectomy. There was no post tonsillectomy bleeding among the 40 patients. Conclusions: Microdebrider intracapsular tonsillotomy is equal to Cold steel dissection tonsillectomy for symptom remedy with a significant reduction in postoperative morbidity. Microdebrider intracapsular tonsillotomy substantially lessen pain and a quicker resumption of a normal diet in comparison with Cold steel dissection tonsillectomy .